Causes and health risk assessment of fluorine in the Red bed groundwater and adjacent geothermal water of the Guang'an Area, Southwest China - Yu-xiang Shao; Wei Zhang; Wen-bin Chen; Li Chen; Jian Li; Guang-long Tian; Li-cheng Quan; Bu-qing Yan; Yu-jie Liu (Journal of Groundwater Science and Engineering)
Understanding the levels, causes, and sources of fluoride in groundwater is critical for public health, effective water resource management, and sustainable utilization. This study employs multivariate statistical methods, hazard quotient assessment, and geochemical analyses, such as mineral saturation index, ionic activities, and Gibbs diagrams, to investigate the hydrochemical characteristics, causes, and noncarcinogenic risks of fluoride in Red bed groundwater and geothermal water in the Guang'an area and neighboring regions. Approximately 9% of the Red bed groundwater samples contain fluoride concentrations exceeding 1 mg·L−1. The predominant water types identified are Cl-Na and HCO3-Na, primarily influenced by evapotranspiration. Low-fluoride groundwater and high-fluoride geothermal water exhibit distinct hydrochemical types HCO3-Ca and SO4-Ca, respectively, which are mainly related to the weathering of carbonate, sulfate, and fluorite-containing rocks. Correlation analysis reveals that fluoride content in Red bed groundwater is positively associated with Na+, Cl−, SO42−, and TDS (r2 = 0.45–0.64, p < 0.01), while in geothermal water, it correlates strongly with pH, K+, Ca2+, and Mg2+ (r2 = 0.52–0.80, p < 0.05). Mineral saturation indices and ionic activities indicate that ion exchange processes and the dissolution of minerals such as carbonatite and fluorite are important sources of fluoride in groundwater. The enrichment of fluorine in the Red bed groundwater is linked to evaporation, cation exchange and dissolution of fluorite, caused by the lithologic characteristics of the red bed in this area. However, it exhibits minimal correlation with the geothermal water in the adjacent area. The noncarcinogenic health risk assessment indicates that 7% (n = 5) of Red bed groundwater points exceed the fluoride safety limit for adults, while 12% (n = 8) exceed the limit for children. These findings underscore the importance of avoiding highly fluoridated red bed groundwater as a direct drinking source and enhancing groundwater monitoring to mitigate health risks associated with elevated fluoride levels.